2022
DOI: 10.3389/fmicb.2022.644146
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Maltodextrin Intake Reduces Virulent Metabolites in the Gut Environment: A Randomized Control Study in a Japanese Cohort

Abstract: In recent years, there have been many reports on the effects of prebiotics on intestinal health. In particular, the consumption of resistant maltodextrin (RMD) has been reported to be beneficial. However, there has been no comprehensive quantification of the effect of RMD on the intestinal environment. Therefore, this study aimed to quantify the effects of RMD on the intestine, especially the intestinal microbiome and metabolome profiles. A randomized, double-blind, and controlled trial was conducted in 29 Jap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, indigestible, fermentable, resistant maltodextrin was proven to have prebiotic functions, as consumption of RMD increased gut microbiota richness, particularly the Bifidobacteria count, and short chain fatty acid (SCFA) production [40][41][42]. Recent reports revealed that when compared to FOS, RDM intake was more efficient in the production of acetate, butyrate, propionate, and total SCFA, as well as lower in trimethylamine synthesis [13,43]. However, evidence was lacking about the impact of RMD on disease prevention, including intestinal epithelium and kidney health.…”
Section: Discussionmentioning
confidence: 99%
“…However, indigestible, fermentable, resistant maltodextrin was proven to have prebiotic functions, as consumption of RMD increased gut microbiota richness, particularly the Bifidobacteria count, and short chain fatty acid (SCFA) production [40][41][42]. Recent reports revealed that when compared to FOS, RDM intake was more efficient in the production of acetate, butyrate, propionate, and total SCFA, as well as lower in trimethylamine synthesis [13,43]. However, evidence was lacking about the impact of RMD on disease prevention, including intestinal epithelium and kidney health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ImP levels were positively associated with saturated fat intake (driven by high cheese intake), and negatively associated with fiber and unsaturated fat intake (driven by reduced intake of vegetables and nuts) ( Molinaro et al, 2020 ). One intervention study conducted by Nishimoto et al demonstrated that the intake of resistant maltodextrin (one of the dietary fibers) could reduce fecal ImP levels among Japanese participants ( Nishimoto et al, 2022 ). For the dietary pattern, serum ImP levels were inversely associated with the alternate Healthy Eating Index, dietary diversity score, and MedDiet score ( Molinaro et al, 2020 ).…”
Section: Microbial Metabolites Provide Functional Connection Between ...mentioning
confidence: 99%
“…A previous study showed that RMD increases intestinal levels of Bifidobacterium in humans (17,18). In addition, a recent study reported that RMD improved the E-mail: akane-kanasaki@matsutani.co.jp gut environment by reducing the production of virulent intestinal metabolites and causing positive alterations of the intestinal microbiota in Japanese humans (19).…”
mentioning
confidence: 99%